Simple and selective method for simultaneous removal of mercury(ii) and recovery of silver(i) from aqueous media by organic ligand 4, 4′-azo-1, 2, 4-triazole. Issue 3 (4th February 2022) - Peng, Panpan; Zhao, Chaofeng; Ji, Jie; Chen, Weixing; Ding, Ning; Li, Shenghua; Pang, Siping
Abstract : Based on coordination chemistry, the removal of Hg 2+ and the recovery of Ag + are achieved simultaneously by selecting the 4, 4′-azo-1, 2, 4-triazole (Atrz) as an organic ligand only through simple mixing, agitation and filtration. Abstract : Conventional methods for extracting heavy metal ions cannot be applied to simultaneously achieve removal of highly toxic metals and recovery of valuable noble metals. Herein, the removal of Hg 2+ and the recovery of Ag + are achieved simultaneously by selecting 4, 4′-azo-1, 2, 4-triazole (Atrz) as an organic ligand. Atrz can form insoluble coordination compounds Atrz@Hg(ii ) and Atrz@Ag(i ) with these two ions in aqueous solution, but only Atrz@Hg(ii ) can dissolve in dimethyl sulfoxide (DMSO). The results of adsorption experiments with single and mixed metals show that Atrz has strong selectivity for Ag + and Hg 2+ and can effectively coordinate with them. This method can also be used to capture other metal ions in the following order: Na +, Ni 2+, Al 3+ < Mn 2+, Cr 3+ < Co 2+, Zn 2+, Fe 3+, Ba 2+ ≪ Cu 2+ < Pb 2+, Ag + and Hg 2+ . In addition, powder X-ray diffraction (PXRD), Fourier-transform infrared (FT-IR) spectroscopy, Raman spectroscopy, and scanning electron microscopy (SEM) proved that Atrz@Hg(ii ) is a coordination compound of Atrz with Hg 2+ . Particularly, the single crystal X-ray diffraction analysis (SXRD) of Atrz@Ag(i ) confirmed the coordination structure. This method, based on coordination interactions and solubility difference, can be used to simultaneously remove and recover different heavy metals using only simple mixing, agitation and filtration. It therefore has excellent potential for application in wastewater treatment, especially in the pretreatment process.